2023
DOI: 10.3390/ma16062373
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Adhesion on Dental Polymers as a Function of Manufacturing Techniques

Abstract: The microbiological behavior of dental polymer materials is crucial to secure the clinical success of dental restorations. Here, the manufacturing process and the machining can play a decisive role. This study investigated the bacterial adhesion on dental polymers as a function of manufacturing techniques (additive/subtractive) and different polishing protocols. Specimens were made from polyaryletherketone (PEEK, PEKK, and AKP), resin-based CAD/CAM materials (composite and PMMA), and printed methacrylate (MA)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Among commercial PEEK dental products, there were no significant differences between injected molded samples and printed samples of PEEK in adhesion of S. sanguinis. In contrast, pressed PEEK samples showed significantly higher adhesion [33]. On the other hand, another bacteria, S. mutans, had no differences in adhesion based on the manufacturing technique [33].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Among commercial PEEK dental products, there were no significant differences between injected molded samples and printed samples of PEEK in adhesion of S. sanguinis. In contrast, pressed PEEK samples showed significantly higher adhesion [33]. On the other hand, another bacteria, S. mutans, had no differences in adhesion based on the manufacturing technique [33].…”
Section: Introductionmentioning
confidence: 88%
“…In contrast, pressed PEEK samples showed significantly higher adhesion [33]. On the other hand, another bacteria, S. mutans, had no differences in adhesion based on the manufacturing technique [33].…”
Section: Introductionmentioning
confidence: 88%
“…A biofilm is a community of microorganisms characterized by bacterial cells that are irreversibly attached to a substratum or interface, or to each other, embedded in a matrix of extracellular polymeric substances that they have produced [ 10 , 11 ]. Researchers have observed that biofilm formation follows a sequential colonization, from early colonizers such as streptococci, to bacterial proliferation, and to the final formation of biofilm [ 12 ], in which surface properties, such as morphology, chemistry, and surface energy, are the main factors affecting interfacial interactions [ 13 , 14 ]. According to the Cassie–Baxter wettability model, superhydrophobic surfaces (characterized by a water contact angle (WCA) of ≥ 150° and sliding angle SA of ≤ 10°) exhibit non-wetting, anti-fouling, and self-cleaning properties, resulting from the combination of low surface energy and surface roughness [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ill-fitting dentures can exert pressure on the soft tissues of the mouth, leading to friction and sore spots [7]. This continuous irritation creates an environment where fungal infections, notably C. albicans, can thrive, contributing to the development of DS [8][9][10][11]. Conversely, properly fitting and wellmaintained dentures can help prevent denture stomatitis.…”
Section: Introductionmentioning
confidence: 99%